1998
DOI: 10.1136/gut.43.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal metaplasia at the gastro-oesophageal junction:Helicobacter pylori gastritis or gastro-oesophageal reflux disease?

Abstract: Conclusion-This study suggests that the pathogenesis of intestinal metaplasia at the SCJ is not uniform: at an endoscopically unremarkable SCJ it is a sequela of H pylori gastritis, but coexisting with endoscopic features of Barrett's oesophagus it is associated with male sex and gastrooesophageal reflux disease. (Gut 1998;43:17-21)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
73
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 29 publications
3
73
1
3
Order By: Relevance
“…Second, more than 95% of patients who had intestinal metaplasia in the present study had intestinal metaplasia originating in the gastric cardia, most of whom had a normalappearing Z line. This contrasts to endoscopy studies, in which the majority of intestinal metaplasia (approximately two thirds in most studies) occurs in short segments of esophageal columnarappearing mucosa identified at endoscopy (5,7,8,11,12). If the stomach, therefore, is the source of intestinal metaplasia in an asymptomatic general patient population, as the present study suggests, then a low rate of adenocarcinoma relative to a high frequency of intestinal metaplasia at the esophagogastric junction is not surprising, given the reduced likelihood of gastric intestinal metaplasia to progress to dysplasia or carcinoma (4 -12).…”
Section: Discussionmentioning
confidence: 82%
“…Second, more than 95% of patients who had intestinal metaplasia in the present study had intestinal metaplasia originating in the gastric cardia, most of whom had a normalappearing Z line. This contrasts to endoscopy studies, in which the majority of intestinal metaplasia (approximately two thirds in most studies) occurs in short segments of esophageal columnarappearing mucosa identified at endoscopy (5,7,8,11,12). If the stomach, therefore, is the source of intestinal metaplasia in an asymptomatic general patient population, as the present study suggests, then a low rate of adenocarcinoma relative to a high frequency of intestinal metaplasia at the esophagogastric junction is not surprising, given the reduced likelihood of gastric intestinal metaplasia to progress to dysplasia or carcinoma (4 -12).…”
Section: Discussionmentioning
confidence: 82%
“…5 However, the pathogenesis of SIM, which is considered to be a precursor for EAC, still remains controversial. [6][7][8][9][10][11] It is a common assumption that an inverse statistically significant relationship of H. pylori infection with both BE and EAC, thus suggesting a protective role of the infection in these entities. 12,13 As for one of the possible mechanisms, a decrease in the acid production through H. pyloriinduced atrophic corpus gastritis, or through hyposecretion in the nonatrophic stomach may influence a reduced risk of these conditions.…”
mentioning
confidence: 99%
“…It has been shown in a number of studies from developed countries that IM is as common as 7-25% in a normal in appearance Z-line (IM-SCJ) in patients referred for upper GI endoscopy (6,(18)(19)(20)(21)(22). This wide range might be related with different patient selection criteria, staining techniques or the characteristics of study areas, such as low prevalence of HP, high income and obesity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the roles of GERD and HP infection in the pathogenesis of IM at the GEJ are confusing and sometimes contradictory. Hackelsberger et al (22) suggested that the pathogenesis of IM at the SCJ is not uniform. They found that IM-SQJ is a sequela of HP gastritis, but endoscopic features BE are associated with GERD.…”
Section: Discussionmentioning
confidence: 99%